The problem with empathy: Justification and appeasement in Hey, Kiddo and Real Friends. Issue 1 (1st November 2021) - Sutton, Danielle
In this article, Danielle Sutton examines the way in which the propensity towards narrative empathy in texts for children ultimately serves to rationalize abuse in two autobiographical comics for young people: Jarrett Krosoczka's Hey, Kiddo and Shannon Hale's Real Friends.